STUDI KELAYAKAN PROYEK PERKEBUNAN KELAPA SAWIT PT. HENRISON INTI PERSADA, PAPUA - BUDIASA, I WAYAN (SOCA: Jurnal Sosial Ekonomi Pertanian, 2012)
The Nucleus Estate and small-holder Development Project (NES-Project) of Elaeis melanococca which is developed in Papua Province (Irian Jaya) is inspired by Henrison Inti Persada Enterprise. It has involved about 5,650 families and covered 19,333 hectares. The NES-Project requires an investment of Rp 231.79 billions. Feasibility study of this project is overlooked from its marketing, technical, operational management, economic and financial aspect. Data analysis includes descriptive and quantitative analysis. The result of study shows that The NES-Project of Elaeis melanococca would be competitive investment according to the investment criteria of Net Present Value (NPV) and Internal Rate of Return (IRR). The project suitability depends on prospective marketing, the available technology, operational management ability, and which can give benefit economically. Financial ratio analysis shows that this project is profitable, liquid, solvent, and efficient, but from the sensitivity analysis, this project seems to be sensitive (especially in The Nucleus Estate), if viewed from the IRR value which only slightly bigger compared to the social discount rate, which expected.
Keywords: NES-Project, Elaeis melanococca (Kelapa Sawit), feasible.